Modelling and implementing emerald gem (game for economical modelling) for behavior hypothesis checking in public goods distribution - Blagaya, D.; Chepiga, D. (ХНУ ім. В. Н. Каразіна, 2012)
This article describes one of the economic experiments for investigation of the free-rider problem. The problem is based on the desire to maximize individual profit by the avoidance of the participation in expenses. Special network software was created for checking behavioral hypotheses in condition of the conflict between individual profit and public benefit. At the beginning of this article you can find description of the experiment and its modifications. After that the main aspects of the software implementation of the experiment are described. Finally, some experimental results are presented. These results correspond with relevant results, described in literature.
В данной статье описан один из экономических экспериментов для исследования так называемой проблемы «безбилетника». Данная проблема проявляется в желании агента получить максимальную выгоду посредством уклонения от участия в затратах. Для проверки поведенческих гипотез при конфликте между индивидуальной выгодой и общественным благом было создано специальное сетевое программное обеспечение. В начале работы описывается суть эксперимента и его модификации. После чего представлены основные аспекты программной реализации эксперимента. В заключительной части приводятся некоторые результаты проведенных экспериментов, которые согласовываются с теоретическими аспектами, описанными в литературе.
Keywords: economical experiment; free-rider problem; behavior of economic agents; hypotheses of a rational choice; cooperation effect; public benefit; network software